Associations between assertiveness, psychological well‐being, and self‐esteem in adolescents. Issue 1 (22nd January 2013) - Sarkova, Maria; Bacikova‐Sleskova, Maria; Orosova, Olga; Madarasova Geckova, Andrea; Katreniakova, Zuzana; Klein, Daniel; van den, Wim; van, Jitse P.
Abstract This study explored the associations between adolescents' assertive behavior, psychological well‐being, and self‐esteem. The sample consisted of 1, 023 students (14.9 ± .51; 47.6% boys). Two dimensions of the Scale for Interpersonal Behavior (distress and performance), 2 factors of the General Health Questionnaire‐12 (depression/anxiety and social dysfunction), and 2 factors of the Rosenberg Self‐Esteem Scale (positive self‐esteem and negative self‐esteem) were used; data were analyzed using hierarchical linear regression. It was found that (a) the more anxious respondents felt in assertive situations, the less frequently they engaged in these situations; and that (b) both dimensions of assertiveness were associated with psychological well‐being and self‐esteem.